Impact of income shock on children's schooling and labor in a West African country - Mafaïzath A. Fatoke-Dato (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
This study measures the impact of a flood in 2010 in Benin on children's schooling and labor. The data used are the National Demographic and Health Surveys (DHS) of 2006 and 2012. The difference in differences estimates points out a significant decrease in income for farm households following the shock. The income shock affected enrollment of girls the most with a decrease in enrollment of 5.99% for girls in rural areas, of 4.45% for boys in rural areas, of 7.76% for girls in urban areas and of 6.17% for boys in urban areas. Meanwhile, the likelihood to be a domestic worker or a farmer has significantly increased. Despite the removal of school fees in 2006, the households still withdrew their children from school after this income shock. These results imply that income shocks could be a threat to the Universal Primary Education.
Keywords: I24; O55; Q54; 330; Natural disasters; Education; Income shock; Child labor